Srining Fitokimia Puding Daun Kelor (Moringa Oleifera ) Sebagai Pelancar Asi - Suryatim Pratiwi, Yopi; Handayani, Sri; Zulfiana, Yesvi (STIKES Yarsi Mataram, 2023)
Diterima 4 Agustus 2023 Diterbitkan 20 Septemeber 2023Key words: Faded leaf pudding, ASI LauncherKata Kunci Puding daun kelor, Pelancar ASIBackground: Breast milk (ASI) is the best nutrition for babies because it is easy to digest and contains nutrients needed for growth and immunity. Exclusive breastfeeding can reduce infant morbidity and mortality. Insufficient breast milk production is a common complaint expressed by mothers, especially in the first week of postpartum. The use of Laktogogum (Laktogogue) is one way that can be done to increase the rate of secretion and production of breast milk. The Moringa plant (Moringa Oleifera) is a local food ingredient that has the potential to be developed by breastfeeding mothers. Moringa leaves can be prepared in the form of pudding. Pudding can be used as an additional alternative food that uses Moringa leaves for breastfeeding mothers. Method: The method in this research is to carry out laboratory tests on Moringa leaf pudding at the Analytical Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Mataram University on May 8 2023. Alkaloid screening uses Mayer and Dragendorff reagents. Results: The research results showed that moringa leaf pudding (Moringa oleifera) contained alkaloid compounds. Conclusion: Utilizing Moringa leaf pudding is an alternative that can be used to overcome the problem of insufficient breast milk production.